Minimally Invasive Therapy for Smile Correction using Gingivoplasty, Tooth Bleaching and Resin Composite Restorations - Soares Xavier de Siqueira, Eric Roberto; Dias, Marlon Ferreira [UNESP]; Cardoso de Oliveira, Aulo Victor; Medeiros Lins, Claudio Eufrasio; Espindola-Castro, Luis Felipe (Premchand Shantidevi Research Foundation, 2022)
A multidisciplinary approach and minimally invasive therapies are essentials to obtain effective results from aesthetic dentistry. Minimally invasive dentistry requires minimal intervention for the placement and replacement of restorations. This paper reports a case of 24-year-old female, who was dissatisfied with her dark and unsatisfactory dental restorations. After the clinical examination, it was proposed to perform a gingivoplasty, tooth bleaching and replacement of the unsatisfactory restorations with resin composite. Initially, the gingivoplasty was performed, which consisted of the following steps- periodontal probing, measurement of new zeniths and marking of bleeding points, internal bevelled incision and removal of the gingival collar with periodontal curettes. After healing period, using the combined technique, in-office bleaching was done with 35% hydrogen peroxide followed by three weeks at-home bleaching with 16% carbamide peroxide. The unsatisfactory restorations were replaced with resin composite according to dental substrate. Sequentially, occlusal adjustment, finishing and polishing with sanding discs and felt discs were performed. The multidisciplinary approach in the execution of the treatment was fundamental for the aesthetic harmonisation of the smile, providing health, well-being of the patient and professional satisfaction.
Keywords: composite resins; Dental aesthetics; Tooth whitening